2013
DOI: 10.5935/0103-507x.20130057
|View full text |Cite
|
Sign up to set email alerts
|

Aortic luminal thrombus and intramural hematoma after cardiopulmonary resuscitation

Abstract: We describe the case of a patient with an intramural hematoma and floating thrombus after cardiopulmonary resuscitation. The 92-year old man had a cardiac arrest due to ventricular fibrillation and witnesses immediately initiated manual cardiopulmonary resuscitation. Transesophageal echocardiography was performed immediately on hospital admission because the patient was in cardiogenic shock. In addition to an akinetic anterior wall, examination of the descending thoracic aorta demonstrated an intramural hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…4,[7][8][9][10][11][12] There are also some cases with rare concomitant disorders that may be the underlying factors of ALFT (Table 3). [13][14][15][16][17][18][19] Some findings on CT may provide clues to explore the cause of lesion. In our study, 4 of 5 ALFTs were attached to the focal thickened walls of aorta with or without calcifications, which suggested the presence of atherosclerotic plaques.…”
Section: Cta Findings Analysis and Etiology Exploration Of Aftmentioning
confidence: 99%
“…4,[7][8][9][10][11][12] There are also some cases with rare concomitant disorders that may be the underlying factors of ALFT (Table 3). [13][14][15][16][17][18][19] Some findings on CT may provide clues to explore the cause of lesion. In our study, 4 of 5 ALFTs were attached to the focal thickened walls of aorta with or without calcifications, which suggested the presence of atherosclerotic plaques.…”
Section: Cta Findings Analysis and Etiology Exploration Of Aftmentioning
confidence: 99%
“…Acute intramural aortic hematomas, which can lead to fatal aortic rupture, 10 have been described as an uncommon complication of CPR. 11 In our case, progression of the size of hematoma demonstrated that lesion happened due to CPR and was not old. Limited reports of these lesions are available, and mostly, aortic lesions after CPR are diagnosed in autopsy.…”
mentioning
confidence: 48%
“…Aortic dissection after CPR has rarely been reported in survivors [11-13]. Most blunt aortic injuries occur in the proximal descending aorta, where the relatively mobile aortic arch joins the fixed descending aorta via the ligamentum arteriosum.…”
Section: Discussionmentioning
confidence: 99%